Nasionalisme-Religius dan Cita Kepemimpinan Nasional dalam Manuskrip Sejarah Kyai Ageng Tegalsari: Religious-Nationalism and National Leadership Imagination in the Manuscript Sejarah Kyai Ageng Tegalsari - Akhlis Syamsal Qomar; Adhie Handika Restu Damara (Besari: Journal of Social and Cultural Studies, 2023)
Events experienced by the Indonesian people often place nationalism and religion on opposite sides. This was marked by the strengthening politicization of identity after the 2014 general election. Issues related to certain ethnicities, ideologies, and religions were used by some elite politicians to build a bad image of their political opponents. Starting from these problems, it is necessary to strengthen the understanding of religious nationalism to strengthen Indonesian nationality which is rooted in the nation's historical legacy in the past. One of these remains is manuscripts that have become a treasure of the Indonesian people. This research uses historical research methods including the heuristic stage by culturally approaching written sources in the form of several manuscripts left in the 19th century at Perdikan Ageng Pesantren Tegalsari of Ponorogo entitled "Sejarah Kyai Ageng Tegalsari". This research aims to find out the concept of religious nationalism in the 19th-century manuscript and what values can be learned.   Peristiwa yang dialami oleh bangsa Indonesia seringkali menempatkan nasionalisme dan agama di sisi yang berseberangan. Hal tersebut ditandai dengan menguatnya politisasi identitas pasca pemilihan umum pada 2014. Isu-isu yang berkaitan dengan etnik, ideologi dan agama tertentu digunakan oleh sebagian elite politisi guna membangun citra buruk lawan-lawan politiknya. Bertolak dari permasalahan tersebut, perlu adanya penguatan paham nasionalisme yang religius guna memperkuat kebangsaan Indonesia yang berakar dari tinggalan sejarah bangsa di masa lalu. Salah satu tinggalan tersebut adalah manuskrip atau naskah kuno yang kaya dan menjadi khazanah bangsa Indonesia. Penelitian ini menggunakan metode penelitian sejarah meliputi tahap heuristik. Pendekatan yang dipakai adalah pendekatan kultural, dengan menggunakan sumber tertulis berupa manuskrip peninggalan Pesantren Perdikan Ageng Tegalsari Ponorogo abad ke-19 yang berjudul “Sejarah Kyai Ageng Tegalsari”. Tujuan penelitian ini ialah mengetahui konsep nasionalisme-religius dalam manuskrip Pesantren Perdikan Ageng Tegalsari Ponorogo abad ke-19 dan apa nilai yang bisa dipetik.